Videos that speak for themselves: when non-extensionists show agricultural videos to large audiences - Bentley, J.; Mele, P.V.; Okry, F.; Zossou, E. (Informa UK Limited, 2014)
In 2008, an NGO showed videos about rice to farmers in 19 villages in Benin. A study in 2013 showed that farmers remembered the videos, even after five years had passed. In most of the villages at least some farmers experimented with rice farming or with new technology after the video screenings, which attracted large audiences of community members, including youth and women. Some of the villagers also visited extension agencies to get rice seed, and occasionally to seek more information. Farmers can benefit from agricultural learning videos shown by organisations with little previous agricultural experience. Videos do not necessarily need to be facilitated by an expert who knows the subject. Sometimes the video can speak for itself.